2010
DOI: 10.1080/01587919.2010.498082
|View full text |Cite
|
Sign up to set email alerts
|

Literature on the safe and disruptive learning potential of mobile technologies

Abstract: Worldwide growth in use of mobile phones has fostered the emergence of mobile learning. Mobile technologies are used both in classrooms to support instruction (safe) and as tools that significantly change instructional activities, learner roles, and learning location (disruptive). Learners become less consumers of information and more collaborators, researchers, and publishers on-the-go (Stead, 2006). Scholarship in m-learning is scarce and lacks rigor (McNeal & van't Hooft, 2006). Even with increasing numbers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 14 publications
1
32
0
1
Order By: Relevance
“…Koszalka and Ntloedibe-Kuswani (2010) suggested that there is a need for more rigorous research on the use of mobile technology in learning to enhance the use of mobile learning in education. Also, there is a need for more extensive quantitative and qualitative research studies on mobile learning to advance the implementation of mobile learning in the 21st century (Ali & Irvine, 2009 …”
Section: Discussionmentioning
confidence: 99%
“…Koszalka and Ntloedibe-Kuswani (2010) suggested that there is a need for more rigorous research on the use of mobile technology in learning to enhance the use of mobile learning in education. Also, there is a need for more extensive quantitative and qualitative research studies on mobile learning to advance the implementation of mobile learning in the 21st century (Ali & Irvine, 2009 …”
Section: Discussionmentioning
confidence: 99%
“…El m-learning, pues, se diferencia del elearning en la medida en que se facilita a través de las tecnologías móviles para estudiantes que son también móviles (Koszalka & Ntloedibe Kuswani, 2010). Y esta tecnología móvil se puede describir como todo dispositivo equipado con capacidad de comunicación inalámbrica pero a la vez pequeño, ligero, fácil de llevar y que nos acompaña en cada momento de nuestra vida cotidiana (Caudill, 2007;Chang, Sheu & Chan, 2003;Fombona, Pascual & Madeira, 2012).…”
Section: Introductionunclassified
“…In addition, ETs are disruptive (e.g., [58]), that is, they have the ability to disrupt the educational context and change or update educational practices for the benefit of learning and teaching. This leads to another characteristic, they are innovative [59]) because they produce changes or transformations in the school from different processes.…”
Section: 5mentioning
confidence: 99%